2016
DOI: 10.1164/rccm.201505-0862oc
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Surfactant Protein-D, Matrix Metalloproteinase-7, and Osteopontin Index Distinguishes Idiopathic Pulmonary Fibrosis from Other Idiopathic Interstitial Pneumonias

Abstract: A biomarker index of SP-D, MMP-7, and osteopontin enhanced diagnostic accuracy in patients with IPF compared with those with non-IPF ILD. Our data suggest that this biomarker index may improve diagnostic confidence in IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 38 publications
9
122
1
5
Order By: Relevance
“…Recently, a biomarker index of SP-D, MMP-7, and osteopontin was found to enhance diagnostic accuracy in IPF patients compared to those with non-IPF interstitial lung diseases [14]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a biomarker index of SP-D, MMP-7, and osteopontin was found to enhance diagnostic accuracy in IPF patients compared to those with non-IPF interstitial lung diseases [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, a biomarker index composed by SP-D, MMP-7, and osteopontin showed to improve diagnostic accuracy of IPF compared to non-IPF ILD [14]. …”
Section: Introductionmentioning
confidence: 99%
“…The versatility of MMP-7 embodies itself a pivotal role in regulating a diverse range of cellular processes, including ECM remodeling and epithelial-mesenchymal transition(EMT) [19, 20]. Not a few studies have reported that upregulation of MMP-7 was found in several fibrosis-related diseases, such as idiopathic pulmonary fibrosis [21], cirrhosis [22]. Moreover, recent publications demonstrated that the renal expression of MMP-7 was enhanced in kidney fibrosis as well, which correlates with β-catenin [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…In pulmonary fibrosis or asthmatic patients, serum Postn levels could efficiently predict a worsened outcome or resistance to therapy (41,42). Moreover, plasma levels of OPN cound distinguish subgroups of lung disease patients (72). In terms of therapy, adenoviral CCN5 overexpression or treatment with a blocking antibody against Postn limited collagen deposition in IPF mouse models (18,40).…”
Section: Matricellular Proteins As Biomarkers or Therapeutic Targets mentioning
confidence: 99%